2022
DOI: 10.33899/ijvs.2021.129798.1688
|View full text |Cite
|
Sign up to set email alerts
|

Ovario-utero protective effect of silymarin in ethidium bromide treated female rats

Abstract: This study was conducted to qualify the ameliorating potency of silymarin against toxicity in ethidium bromide (EtBr) treated female rats. Eighty female Wistar rats aged 100 days, weighted 170-175 g were randomly allocated to control, orally supplemented with drinking water, and three treated groups, orally supplemented with silymarin 200 mg/kg BW, EtBr 10 mg/kg BW, and combination of EtBr and silymarin (SEtBr), respectively. Each group was allocated to two subgroups, sacrificed after 20 and 40 days of treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…The reduction of oxidative stress and the regulation of lipid components were found to be crucial variables in enhancing fertility (25). Moreover, exposure to many environmental toxins may harm fertility (26,27). High doses of MIONPs may be a hazardous inducer of male infertility, according to the present findings, which might be due to a direct influence on spermatogenesis or indirectly through higher centers in the brain.…”
Section: Discussionsupporting
confidence: 53%
“…The reduction of oxidative stress and the regulation of lipid components were found to be crucial variables in enhancing fertility (25). Moreover, exposure to many environmental toxins may harm fertility (26,27). High doses of MIONPs may be a hazardous inducer of male infertility, according to the present findings, which might be due to a direct influence on spermatogenesis or indirectly through higher centers in the brain.…”
Section: Discussionsupporting
confidence: 53%
“…This decline negatively affected the growth and development of the ovaries, as well as a decrease in their functions in oogenesis and folliculogenesis and a decrease in their ability to manufacture reproductive hormones (estrogen and progesterone). It has been mentioned that estradiol and progesterone have vital regulatory roles in the estrous cycle (16,17). Zarifkar et al (18) found decreased estradiol and progesterone levels in female rats daily orally administered with levothyroxine (100µg/100g b.w) for ten days.…”
Section: Discussionmentioning
confidence: 99%